THE EFFECTS OF Ni2+ AND Cr3+ ON THE CONTENTS OF CHLOROPHYLL, PROTEIN, ABSCISIC ACID AND PROLINE IN BEAN (Phaseolus vulgaris cv. Strike) SEEDLINGS - Zengin, Fikriye Kirbag (Parlar Scientific Publications (P S P), 2009)
The aim of this study was to investigate the levels of chlorophyll, abscisic acid (ABA), total protein and proline of bean plants (Phaseolus vulgaris cv. Strike) in the presence of nickel and chromium. Control, Ni and Cr-treated plants were grown for 192 h in Hoagland solution. Samples were taken at 48-h intervals. Chlorophyll (a+b), total protein and proline contents of 10-days-old primary leaves were determined by a spectrophotometer. ABA contents in roots and leaves of the seedlings were measured by HPLC. Elevated Ni and Cr levels increased the ABA contents in roots and leaves of seedlings. An increase of proline in the leaves of seedlings exposed to nickel and chromium occurred, as well as a decrease of chlorophyll (a+b) and total protein contents (p<0.05 or p<0.01).
Keywords: Abscisic acid; chlorophyll; heavy metal; proline; protein